2002
DOI: 10.4049/jimmunol.169.8.4417
|View full text |Cite
|
Sign up to set email alerts
|

Role of STAT6 and Mast Cells in IL-4- and IL-13-Induced Alterations in Murine Intestinal Epithelial Cell Function

Abstract: Gastrointestinal nematode infections generally invoke a type 2 cytokine response, characterized by the production of IL-4, IL-5, IL-9, and IL-13. Among these cytokines, IL-4 and IL-13 exhibit a functional overlap that can be explained by the sharing of a common receptor or receptor component (IL-4Rα). Binding of IL-4 by either the type 1 or 2 IL-4R, or of IL-13 by the type 2 IL-4R, initiates Jak-dependent tyrosine phosphorylation of the IL-4Rα-chain and the transcription factor, STAT6. In the present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
159
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(178 citation statements)
references
References 36 publications
17
159
0
2
Order By: Relevance
“…IL-25 is a potent inductor for the production of IL-4, IL-5, and IL-13 (8). These Th2 cytokines, particularly IL-4 and IL-13, previously have been reported to cause a number of changes in intestinal epithelial functions, such as balance of ion, mucosal fluids absorption (15), and increase in intestinal smooth muscle contraction (16). IL-13 was found primarily to mediate massive histological changes in the gastrointestinal mucosa of mice treated with rIL-25 (8).…”
Section: Discussionmentioning
confidence: 99%
“…IL-25 is a potent inductor for the production of IL-4, IL-5, and IL-13 (8). These Th2 cytokines, particularly IL-4 and IL-13, previously have been reported to cause a number of changes in intestinal epithelial functions, such as balance of ion, mucosal fluids absorption (15), and increase in intestinal smooth muscle contraction (16). IL-13 was found primarily to mediate massive histological changes in the gastrointestinal mucosa of mice treated with rIL-25 (8).…”
Section: Discussionmentioning
confidence: 99%
“…Their further work (37) revealed an increase in chloride ion secretion by infected tissue in response to externally applied histamine, serotonin, and prostaglandin E2, three factors produced by mast cells. Equally, Madden et al (38) showed that WT mice but not mast cell-deficient mice respond to IL-4 by increasing chloride secretion after either histamine or prostaglandin E2 stimulation in vitro. Their data support our demonstration that mast cells are crucial for increased mucosal permeability during T. spiralis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ Secretion-IL-13 is a key Th2 cytokine that has been implicated in aspects of intestinal function (7,27). To delineate the effect of increased intestinal IL-13 on small intestinal barrier function, we examined the resistance across the mucosa (resistance) and ion conductance through ex vivo measurements of I sc across the jejunum of iIL-13Tg and littermate WT mice.…”
Section: Overexpression Of Il-13 In the Small Intestine Up-regulates CLmentioning
confidence: 99%